Menggali Potensi Desa Karang Tunggal melalui Focus Group Discussion (FGD) dengan Masyarakat Lokal - Kaharap, Yogen; Suryanatha, Ida Bagus (Abdimas Indonesian Journal, 2024)
This service aims to explore the potential of Karang Tunggal Village through Focus Group Discussion (FGD) with the active participation of the local community. This study will comprehensively explain how follow-up can be triggered from data analysis in the field and can be heard collaboratively with the Company, the Village Government and of course with the involvement of the community to synergize with each other to build Karang Tunggal Village. Focus Group Discussion (FGD) is one of the qualitative data collection methods that involves a group of people to discuss certain topics, In this service, FGD is expected to provide in-depth insight into the potential of Karang Tunggal Village from the perspective of the local community. (Rejeki et al., 2024). This FGD session lasted approximately 4 hours which was divided into the first 2 hours was the delivery of material by the Head of the Research Team, Mr. Yorgen Kaharapan Nahan., M.Si. The focus was on discussing the main problems that cause a large number of unemployed and explaining the causes of poverty. In addition, it discusses village problems and solutions to problems and explains how to make clear village planning as well as to develop useful villages and how to use finance correctly with openness or transparency. The village government needs to facilitate community participation in formulating programs that suit their real needs. The development of local products and training of MSMEs must be the main focus so that the community can maximize existing resources. The plantation sector as the highest income livelihood also needs to be encouraged to be optimized through modern technology and sustainable agricultural practices.